HUBUNGAN PERSEPSI MASYARAKAT TERHADAP PEMERINTAH DENGAN KECEMASAN MENGHADAPI RENCANA PEMBANGUNAN JALUR GANDA KERETA API - Budi Cakra Buana; Udi Rosida Hijrianti (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2019)
The perception of the public toward the government is a view of each community will be given by the government policy either positive or negative perceptions. The negative perception trigger feelings of tension, heart palpitations, sweaty body, and anxiety. Thus, the purpose of this study is to investigate the correlation between the public perception of government with anxiety encounter the development plan of double track railway toward Pulosari citizens, Blimbing Malang city. The method that used in this study was quantitative correlation method, by using purposive sampling technique. The subjects in this study were 77 Pulosari citizens who reside in the railroad. The scale that used in this study was perception and anxiety scale. The results of the data analysis that used pearson product moment was (r = -0,74 p = 0,01). It is mean that there was a negative correlation between the public perception of government with anxiety encounter the development plan of double track railway. Thus, more positive their perception toward the government, then it did not cause anxiety.